Observation of high dielectric constants in x (Pb (Zn13 Nb23) O3 - (0.2-x) Pb (Ni13 Nb23) O3 -0.8Pb (Zr12 Ti12) O3 ternary solid solutions - Sucheewan Nabunmee (2018)
In the present work, we demonstrate the results of combining two excellent ferroelectric materials at their morphotropic phase boundary compositions, i.e., 0.2 (Pb (Zn13 Nb23) O3 -0.8Pb (Zr12 Ti12) O3 (0.2PZN-0.8PZT) and 0.2Pb (Ni13 Nb23) O3 -0.8Pb (Zr12 Ti12) O3 (0.2PNN-0.8PZT) to form a ternary solid solution of x (Pb (Zn13 Nb23) O3 - (0.2-x) Pb (Ni13 Nb23) O3 -0.8Pb (Zr12 Ti12) O3 (xPZN- (0.2-x) PNN-0.8PZT) which exhibits superior dielectric properties. Examination of the dielectric spectra indicated that the ternary system exhibits a very high relative permittivity of 49 800 (at 10 kHz) for the composition at x=0.10. In addition, an increased amount of PZN was observed to enhance the ferroelectric properties of the system. © 2007 American Institute of Physics.